2021
DOI: 10.3389/fneur.2020.578753
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of 18F-Flutemetamol PET in Patients With Cognitive Impairment and Suspected Alzheimer's Disease: A Multicenter Study

Abstract: Background: In clinical practice, equivocal findings are inevitable in visual interpretation of whether amyloid positron emission tomography (PET) is positive or negative. It is therefore necessary to establish a more objective quantitative evaluation method for determining the indication for disease-modifying drugs currently under development.Aims: We aimed to determine cutoffs for positivity in quantitative analysis of 18F-flutemetamol PET in patients with cognitive impairment and suspected Alzheimer's disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 24 publications
0
25
0
1
Order By: Relevance
“…Equivocal ndings are thus inevitable and lead to interrater variability in visual interpretation [1] because raters have their own experience and potential internal criteria. In addition, in our previous multicenter study using 18 F-utemetamol [2], disagreement between two raters was observed in 9% of cases. Equivocal ndings should be avoided when determining the indication for the disease-modifying drugs currently in development.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Equivocal ndings are thus inevitable and lead to interrater variability in visual interpretation [1] because raters have their own experience and potential internal criteria. In addition, in our previous multicenter study using 18 F-utemetamol [2], disagreement between two raters was observed in 9% of cases. Equivocal ndings should be avoided when determining the indication for the disease-modifying drugs currently in development.…”
Section: Introductionmentioning
confidence: 80%
“…The study participants comprised 24 patients (15 men and 9 women; age range, 48-90 years) enrolled in a previous multicenter study [2]. They were recruited from an outpatient memory clinic of the National Center of Neurology and Psychiatry, Japan.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equivocal findings are thus inevitable and lead to interrater variability in visual interpretation [ 2 ] because raters have their own experience and potential internal criteria. In addition, in our previous multicenter study using 18 F-flutemetamol [ 3 ], disagreement between two raters was observed in 9% of cases. Equivocal findings should be avoided when determining the indication for the disease-modifying drugs currently in development.…”
Section: Introductionmentioning
confidence: 95%
“… Florbetapir (FDA approved in 2012) Flutemetamol (can objectively evaluate amyloid positivity. [ 30 ] …”
Section: Amyloid Molecular Imaging (Positron-emission Tomography)mentioning
confidence: 99%